Sastra Anak Berbasis Kearifan Lokal Banten untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Yoma Hatima (FKIP UNSULTRA, 2026)
This study aims to analyze the effect of using children's literature based on Bantenese local wisdom on elementary school students' reading comprehension. This study used a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The study subjects were 60 fifth-grade elementary school students, consisting of 30 in the experimental group and 30 in the control group. The experimental group received reading instruction using children's literature based on Bantenese local wisdom, while the control group used conventional reading materials from Indonesian language textbooks. Data collection techniques included reading comprehension tests, observation, and documentation. Data were analyzed using descriptive and inferential statistics with independent samples t-tests after meeting prerequisite tests for normality and homogeneity. The results showed that students' reading comprehension skills in the experimental group improved significantly compared to the control group. The average score for the experimental group increased from 62.10 in the pretest to 82.35 in the posttest, while the control group's score increased from 61.75 to 70.40. The results of the hypothesis test showed a t-value of 8.21 with a significance level of 0.000 (p < 0.05), indicating a significant difference between the two groups. This finding indicates that the use of children's literature based on Bantenese local wisdom is effective in improving elementary school students' reading comprehension skills. The integration of stories containing local cultural values ​​not only improves students' literacy skills but also strengthens their understanding of regional cultural values.